2012
DOI: 10.2174/187152812803250999
|View full text |Cite
|
Sign up to set email alerts
|

Non-Selective Inhibition of Cyclooxygenase Enzymes by Aminoacetylenic Isoindoline 1,3-Diones

Abstract: The reported pharmacological activities of acetylenic and phthalimide groups promoted our interest to synthesize a novel series of N-[4-(t-amino-yl)-but-2-yn-1-yl] isoindoline-1,3-diones as anti-inflammatory compounds. The aim of this research is to investigate the selectivity of two compounds, ZM4 and ZM5, on inhibiting cyclooxygenase (COX) in vitro and in silico as well as reducing carrageenan-induced edema in rats. Oral administration of 5-20 mg/kg ZM4 and ZM5 reduced significantly carrageenan-induced edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Conversely, ZM5 showed less pronounced activity in the late formalin phase ( P > 0.05) which again reflects the superiority of ZM4 in reducing acute and chronic pain. Nevertheless, such conclusion should not reflect the less anti-inflammatory ability of ZM5 as we have recently reported that ZM5 showed comparable anti-inflammatory effects to diclofenac and celecoxib in rat paw edema test and enhances the production of transforming growth factor- β from T regulatory cells as compared with other tested compounds [11, 13, 14]. Therefore, it could be suggested that ZM5 has slow rate of absorption through gastrointestinal tract since it neither showed any anti-inflammatory effect during the first hour after carrageenan paw edema induction nor any significant reduction in the late phase of formalin test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, ZM5 showed less pronounced activity in the late formalin phase ( P > 0.05) which again reflects the superiority of ZM4 in reducing acute and chronic pain. Nevertheless, such conclusion should not reflect the less anti-inflammatory ability of ZM5 as we have recently reported that ZM5 showed comparable anti-inflammatory effects to diclofenac and celecoxib in rat paw edema test and enhances the production of transforming growth factor- β from T regulatory cells as compared with other tested compounds [11, 13, 14]. Therefore, it could be suggested that ZM5 has slow rate of absorption through gastrointestinal tract since it neither showed any anti-inflammatory effect during the first hour after carrageenan paw edema induction nor any significant reduction in the late phase of formalin test.…”
Section: Discussionmentioning
confidence: 99%
“…This unique combination represents a new series of compounds as potential anti-inflammatory agents as has been shown to reduce carrageenan-induced paw edema and structurally differs from the generally used drugs that contain acidic, enolic, sulfonamide, or sulfon groups which should exclude the direct insult on the gastrointestinal [11]. Of all the molecules reported in our previous studies, ZM4 and ZM5 were found to possess the best COX-2 inhibition activities, better in reducing carrageenan-inducing inflammation, and modulate proinflammatory and anti-inflammatory cytokines [11, 13, 14] and therefore were selected for further efficacy and safety investigations. The aim of the present study therefore is to study the analgesic activity of these compounds in addition to studying their toxicity and ulcerogenic effect on the stomach following single and repeated administration.…”
Section: Introductionmentioning
confidence: 99%
“…Since these compounds were found to be potentially safe and do not show any stomach irritations [9,10], the current findings should open the door for further studies to show the possibility of utilizing the basic aminoacetylenic isoindolines in autoimmune mediated inflammatory diseases.…”
Section: Discussionmentioning
confidence: 79%
“…When ZM compounds were introduced to LPS-stimulated CD4+ CD25+ve cells, only ZM5 enhanced TGF-β production, whereas ZM2 and ZM4 suppressed such production, suggesting that the structure difference in the ring size and conformational of the cyclic amine ring size, and lipophilicity may be the reasons in different modulations of LPS-TLR-4 TGF-β production signaling pathways. For instance, the azepan ring in ZM5 and the steric factor neighboring the basic nitrogen in ZM4 over ZM3 could be the reasons in activating downstream pathways to inducing anti-inflammatory cytokine TGF-β1 and therefore enhancing the anti-inflammatory activities [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation